Comparison of the Antibacterial effect of Diapaste with Sealapex and Zinc Oxide-Eugenol (ZOE) on Enterococcus Faecalis: A Laboratory Study - Reza Bahram Abadi; Ali Bagherian; Somayeh Khoramian Tusi; Behnam Zeynali
Introduction: The antiseptic characteristic of root canal filling materials seems very critical in pulpectomy procedure to eliminate residual pathogens of root canals. The aim of this laboratory study was to compare the antibacterial activity of a newly introduced premixed calcium hydroxide root canal filling paste of deciduous teeth (Diapaste) with Zinc Oxide-Eugenol (ZOE) and Sealapex on Enterococcus faecalis. Materials & Methods: In this study, agar diffusion inhibitory test was used to assess antibacterial activity. Ten 10-cm-diameter dishes with 4.0mm thickness of agar inoculated with Enterococcus faecalis were used and four 5-mm-diameter wells per dish at equidistant points were filled with the three test root canal filling materials (Diapaste, ZOE and Sealapex) and distilled water as a negative control was used to fill the fourth well. After incubation of the plates at 37oC for 48 hours, the diameter of the zones of bacterial growth inhibition produced around the wells was measured (in mm) with a caliper. Data were analyzed by Kruskall-Wallis test and Mann-Whitney U test. Results: Kruskall-Wallis test indicated that there were statistically significant differences (P<0.001) among median of the zones of bacterial growth inhibition produced by the three different materials. Mean diameter of inhibition zones of bacterial growth was significantly higher in Diapaste than Sealapex (P<0.001) and ZOE (P<0.001). Conclusion: With respect to the limitations of an in vitro study, it appears that Diapaste has more antibacterial activity than ZOE and Sealapex.